Pola Usahatani Terpadu Kelapa, Pandan dan Ternak untuk Meningkatkan Pendapatan Petani di Desa Sindang Jaya, Tasikmalaya, Jawa Barat - DEDI SOLEH EFENDI (Buletin Palma, 2010)
Integrated Coconut, Pandan, and Cattle Farming System to IncreaseFarmer Income in Sindang Jaya Village, Tasikmalaya, West JavaThis research was achieved at investigating the integration of + pandan + cattle in coconut farming in Tasikmalaya regency. Economy and technical data are taken from 30 farmer who joined COGENT (coconut genetic resources network). This research used descriptive survey withr purposive sampling. The income of the correspondent farmer was evaluated before and after COGENT project (2006-2008). Coconut farm income increased 81,71 percent in two years, pandan farm income increased 29,62 percent and sheep cattle income increased 85,77 percent. The farmer income all together increased 91,60 percent from Rp. 2.743.500 to Rp. 5.257.800. Statistical analysis show that sheep cattle in Tasikmalaya with 0,01 credibility give 0,239 correlation point which means that every sheep cattle breeder can increase the farmer income as much as 23 percent. Statistical test result showed that coconut, pandan and cattle farming system can give a significant point before and after the program.